Diseño de un Sistema de Climatización Aplicando la Norma FAIAR de Calidad de Aire Interior para el edificio de Acaire en Bogotá D.C. (2019)
The Colombian Association of Air Conditioning and Refrigeration, promoting knowledge in the efficient use of air conditioning systems in buildings, I seek the support of universities for the implementation of the “FAIARstandard of air quality control in interior in buildings”, Which specifies the process necessary to assess the Indoor Air Quality and establishes the compliance requirement regarding air pollutants and the temperature and humidity necessary to achieve a comfortable space.